Development of a comprehensive stress assessment tool for Indian public sector employees - Pradip Kumar Nanda; G. Nagasubramaniyan (Future Business Journal)
Abstract The study aims to develop a comprehensive stress assessment tool for Indian public sector employees, considering unique stressors, cultural factors, and organizational characteristics. The study employed a deductive approach, cross-sectional design, and mixed-method study based on comprehension of extant stress management theories, to explore the factors contributing to employee stress. The study found that technological disruptions, austerity measures, blame games, multitasking, and work–life balance are significant factors of assessing employee stress. The findings of the study fill the gaps in extant literature and extends support to the job demand control and support model. The findings make practical contributions in assisting practitioners and policymakers to design suitable intervention programs to reduce employee stress and enhance employee productivity. The unique contribution of the study is, first of its kind in the Indian public sector context, that the tool has the potential to assess employee stress effectively at workplace and practitioners can derive benefits of the stress assessment tool. Graphical abstract